SOCIO-ECONOMIC AND GEOGRAPHICAL DETERMINANTS OF FINANCIAL INCLUSION IN CAMEROON - Christophe KUIPOU TOUKAM, Severin TCHIO SEZINE & Alexis TIOMELA YEMEDJEU (International Journal of Research Science and Management, 2020)
The purpose of this article is to identify the socio-economic and geographic determinants of financial inclusion in Cameroon. In terms of methodology, the data used come from two Global Findex databases in 2011 and in 2014 built by the World Bank. Multiple correspondence analysis (MCA) allowed us to transform the qualitative variables of financial inclusion into a composite index of access and use of financial services for each individual. The respective application of the dissimilarity index method and the multiple linear regression model allowed us to highlight the different determinants. Ultimately, the results show us that socioeconomic and geographic factors (income, education, gender, age, area of residence) determine financial inclusion.Following these results, we recommend that the state authorities set up a banking plan which consists in finding the means which allow the population to have a bank account and to have easy access to formal financial services in order to reduce the income inequality. Particular attention must be paid to school infrastructure in rural areas to avoid the long distances to be traveled which delay the first registration of children at school age.